Bracketing the Age of Freshwater Carbonate Formation by OSL Dating Near Lake Kolon, Hungary - Sipos, György; Tóth, Orsolya; Pécsi, Eszter; Bíró, Csaba (Journal of Environmental Geography, 2014)
Freshwater carbonates are unique depositions in the centre of the Carpathian Basin, with debated origin and age. Their formation on the sand covered area of the Danube-Tisza Interfluve is mainly related to lakes appearing in low lying interdune areas from time-totime. Carbonate deposition is governed by various processes, but in general it can be traced back to climatic and concomitant surface and subsurface hydrological variations. Therefore marl, limestone and dolomite layers can be a marker of environmental change. To identify the type of environmental change they may indicate absolute or numerical ages are needed. In previous studies this issue has been addressed by the means of radiocarbon dating. In the present study we attempted to bracket the age of freshwater carbonate formation with the help of optically stimulated luminescence dating and compared our results to radiocarbon data from the literature. In general, the luminescence properties of the investigated samples proved to be suitable for determining the age of the bedding and covering sediments. OSL dates confirmed previous interpretations that freshwater carbonate formation in the area could have a peak around 10,5 ka. However, the termination of the deposition could not be unambiguously determined at the present stage of the analysis. The compound geomorphology and sedimentology of the study area call for further investigations.